The influence of traditional and value based performance measures on shareholder’s value creation of Malaysian listed construction companies - Panigrahi, Shrikant (2016)
This thesis examines the relationship between performance measurement tools and shareholder's wealth in the context of Malaysian public listed construction companies. The question guiding this study is focused on whether the development of performance measures had any impact on shareholder's value. After more than one decade of the Asian financial crisis, Malaysian firms still focus on the conventional performance measures which are criticized due to general accepted accounting principles. Both traditional accounting measures and economic measures have failed in reflecting the company's true value due to lack of creating long term sustainability of business. Thus, this study investigates the long run causal relationship between the performance measurement tools and shareholder's wealth creation. The study exploits panel data analysis techniques particularly Error Correction Models (ECM) to test for the existence of a relationship of error terms. Using a sample of panel data of 280 observations over the period 2003-2012, this study finds compelling evidence that shareholder value is a function of performance measures. The evidence obtained from the study shows the existence of co-integration between the EPS, EVA, DPR MVA and CSV in the short as well as the long run. The study found a strong impact of EPS, EVA and management's dividend payout decisions on created shareholder's value. It was also evidenced that dividend paid to the shareholders and increase market price of shares have significant influence on long term market value of stocks which in turn increases shareholders wealth. EPS is still considered to be the strong factor for the shareholders to identify their value. EVA as a value based performance tool dominates shareholder's wealth. The more the managers produce EVA, the more shareholder's wealth maximization will be created. The finding showed significant support for EVA, but EVA was not reported by the companies and is not been used by investors for their investment decisions. EVA can be utilized as a reward system for increasing management performance. These results conclusively support the claims made by EPS, EVA and DPR proponents and further support the potential usefulness of the performance metric for internal and external performance. Furthermore, MVA was found to have negative relationship with CSV which was contradicting with the theory that shed light on the increase in shareholder value when there is increase in stock market value and efficiency. Thus it is highly recommended to focus for future research on this contradict finding.